Pengembangan Modul Berbasis Proyek Melalui Eksplorasi Budaya Makanan Tradisional Tionghoa Kue Keranjang pada Materi Bangun Ruang Tabung dalam Meningkatkan PemahamanKonsep Siswa SMP - Griffit Spanyer. I. Nababan; Hardi Tambunan; Ruth Mayasari Simanjuntak (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop a Project-Based Learning (PjBL) module integrated with ethnomathematics by utilizing Nian Gao (Chinese New Year cake) as a cultural artifact representing the geometric concept of a cylinder to enhance junior high school students’ conceptual understanding of solid geometry. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The participants were junior high school students in Kelapa Gading, North Jakarta, Indonesia. Data were collected through expert validation sheets, student response questionnaires, classroom observations, interviews, and pre-test and post-test assessments. The data were analyzed using descriptive qualitative and quantitative methods based on mean scores and percentage analysis. The results revealed that the developed learning module obtained an average expert validation score of 4.56, indicating that it was highly feasible for classroom implementation. The implementation of the PjBL module actively engaged students in observing, measuring, and identifying the geometric elements of a cylinder through hands-on exploration of Nian Gao. This contextual learning approach significantly improved students’ conceptual understanding of solid geometry, enhanced their learning engagement and spatial reasoning, and encouraged meaningful learning experiences. Furthermore, integrating ethnomathematics into mathematics instruction fostered students’ appreciation of Chinese Indonesian cultural heritage, thereby supporting both mathematics learning and character education. Therefore, the developed ethnomathematics-based PjBL module is an effective and feasible instructional resource for promoting meaningful, contextual, and culturally responsive mathematics learning.